2014
DOI: 10.1161/circulationaha.113.005479
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Pacemaker Implantation After Transcatheter Aortic Valve Implantation

Abstract: T ranscatheter aortic valve implantation (TAVI) has become the treatment of choice for patients with aortic stenosis who are considered to be nonoperable and a good alternative for those at high surgical risk.1 However, the occurrence of some periprocedural complications remains a concern. The need for permanent pacemaker implantation (PPI) after the procedure is one of the most frequent complications associated with TAVI, with an overall incidence of ≈15% (≈25% and 7% after TAVI with self-expandable valves [S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
170
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 275 publications
(187 citation statements)
references
References 43 publications
12
170
4
1
Order By: Relevance
“…This is an important finding as NOP-LBBB can associate with lack of improvement in left ventricular ejection fraction, poorer functional status, and may also increase the risk of sudden death, especially in those patients with larger QRS. [18][19][20][21] Furthermore, a recent systematic review and meta-analysis including 17 studies showed that new-onset LBBB post TAVR is a marker of an increased risk of cardiac death and the need for permanent pacemaker implantation at 1-year follow-up. 21 Of note, in a previous analysis of the Brazilian registry, with fewer patients and mostly with the CoreValve bioprosthesis, BAVP was associated with an increased need for permanent pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding as NOP-LBBB can associate with lack of improvement in left ventricular ejection fraction, poorer functional status, and may also increase the risk of sudden death, especially in those patients with larger QRS. [18][19][20][21] Furthermore, a recent systematic review and meta-analysis including 17 studies showed that new-onset LBBB post TAVR is a marker of an increased risk of cardiac death and the need for permanent pacemaker implantation at 1-year follow-up. 21 Of note, in a previous analysis of the Brazilian registry, with fewer patients and mostly with the CoreValve bioprosthesis, BAVP was associated with an increased need for permanent pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Atrioventricular block requiring pacemaker implantation is reported in 1% to 8% of patients with the Edwards SAPIEN valve and 19% to 42% with the Medtronic CoreValve using currently available devices. 236 The need for pacemaker implantation did not influence subsequent survival after TAVR in some studies, 237 although others have shown increased mortality in those receiving a new pacemaker. 238 Clinical predictors of complete heart block 239 include characteristics of patient status (valve calcification and preexisting right BBB) 240 and comor bidities, as well as characteristics of the procedure (depth of implantation, device profile) 241 and balloon sizing.…”
Section: Transcatheter Structural Interventionsmentioning
confidence: 98%
“…18 As of this writing, most patients will receive a PPM within 1 week of TAVR for high-degree or CHB. 19 However, careful review of PPM indications from procedure reports from the PARTNER registry revealed a diagnosis of sick-sinus syndrome in 17 % of patients, higher than found in previously published reports. Additionally, there was a noticeable difference in PPM rates between the continued access registry and randomised trial (9.6 % versus 5.6 %), indicating that PPM insertion is partly driven by variable physician threshold.…”
Section: Timing Of Ppm Implantmentioning
confidence: 75%